Alendronate partially rescues the periodontal defects in OIM mouse model of osteogenesis imperfecta - Chen, Po-Jung; Wang, Ke; Lin, Meng-Hsuan; Sharma, Radhika; Kalajzic, Zana; O’Brien, Mara; Yadav, Sumit (Scientific reports, 2025)
Osteogenesis imperfecta (OI) is a fairly common generalized connective disorder characterized by low bone mass, bone deformities and impaired bone quality that predisposes affected individuals to musculoskeletal fragility. Periodontal ligament (PDL)-alveolar bone and PDL-cementum entheses’ roles under OI conditions during physiological loading and orthodontic forces remain largely unknown. In addition, bisphosphonates (e.g., alendronate) are commonly used therapeutics for the treatment of OI. Our knowledge, in terms of the affects of alendronate treatment on the PDL entheses in OI is also far from complete. In this study, we identified craniofacial skeletal defects in an osteogenesis imperfecta ( oim ) murine model of OI. Relative to wild-type littermates, oim mice were found to have decreased skull length, cranial height/width/length, nose length, nasal length, and frontal length. Next, we discovered that oim mice exhibited defects in several dental structures, including short roots and decreased volumes of the alveolar bone, dentin, and cellular cementum. Further, we specifically investigated periodontal defects in the oim mice. Alveolar bone loss in oim mice was primarily associated with elevated bone resorption due to an increased osteoclast number, along with reduced bone formation related to increased sclerostin (SOST) expression. PDL fibers in oim mice were disrupted and discontinuous, while Sharpey’s fibers at the PDL-bone entheses were reduced. Mechanism-based studies showed that catabolism of the PDL was elevated in oim mice, as revealed by an increase in MMP13 and CTSK expression. Meanwhile, the quality of the collagen fibers were impaired in oim mice due to a large accumulation of uncleaved collagen I fibers. With alendronate treatment, however, we could partially rescue these phenotypes. This study, for the first time, characterized periodontal defects in oim mice, detailed craniofacial defects and demonstrated the effectiveness of alendronate in partially restoring these defects.